Respuesta :
i love these kind of questions :D
okay so lets write our problem down 1st:
(-3÷2)x-9=27
okay so you take one of your answers lets do A 1st and put is as x like this:
(-3÷2)-24x(-9)=27 now solve:
(think of PEMDAS)
P = perenthesis
E = exponents (which you dont have in this problem)
M = multiply
D = divide
A = add
S = subtract
do perenthesis 1st which would be (-3÷2)
(-1.5)-24x(-9)
now multiply 24x(-9)
(-1.5)-216 = (-214.5) does it equal -24 (which was what you plugged in for x)
no it doesnt so A cant be your answer. now do it for the rest of your answers :D